2021
DOI: 10.1038/s41598-021-85780-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of arsenic-induced cardiovascular disease susceptibility with genetic polymorphisms

Abstract: Inorganic arsenic (iAs) exposure has been reported to have an impact on cardiovascular diseases (CVD). However, there is not much known about the cardiac tissue injury of CVD patients in relation to iAs exposure and potential role of single nucleotide polymorphisms (SNPs) of genes related to iAs metabolism, oxidative stress, endothelial dysfunction and inflammation which may play important roles in such CVD cases. In this dual center cross-sectional study, based on the exclusion and inclusion criteria, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The effects of As exposure on CVD and CHD in particular was shown to be dose-dependent [40]. A significant influence of AS3MT, NOS3, ICAM1, VCAM1, SOD2, and APOE gene polymorphisms on the interaction between As exposure and CHD was demonstrated [41].…”
Section: Discussionmentioning
confidence: 93%
“…The effects of As exposure on CVD and CHD in particular was shown to be dose-dependent [40]. A significant influence of AS3MT, NOS3, ICAM1, VCAM1, SOD2, and APOE gene polymorphisms on the interaction between As exposure and CHD was demonstrated [41].…”
Section: Discussionmentioning
confidence: 93%
“…They also showed a significant correlation between the accumulation of iAs and As3MT, nitric oxide synthase (NOS3), intercellular adhesion molecule-1 (ICAM1), and superoxide dismutase (SOD2) genotypes. 256 A retrospective study in a Chilean population found for the medium exposure categories (60–623 μg/L) and higher (>623 μg/L), a hypertension OR of 1.49 (95% CI: 1.09; 2.05) and 1.65 (95% CI 1.18, 2.32), respectively. Similar results were observed when analyzing cumulative lifetime exposure.…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…Several epidemiological studies have showed the link between chronic arsenic ingestion and various cardiovascular disorders, including peripheral vascular disease, ischemic heart disease, aterosclerosis, 255 and hypertension. 256,257 A study evaluated the association of mean arsenic concentrations (<1 and 118 μg/L) in drinking water with cardiovascular mortality in the Spanish population. Compared with the total Spanish population, cardiovascular mortality rates increased in municipalities with arsenic drinking water concentrations >10 μg/L.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term exposure to high levels of iAs in drinking water has been linked with skin disorders and increased risk of diabetes, high blood pressure, and several types of cancer. iAs and As compounds are considered to be carcinogenic [ 36 , 37 ].…”
Section: Facts Of Arsenic Exposurementioning
confidence: 99%